Understanding the prognosis and progression of soft tissue sarcoma in the dog : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University, Manawatū, New Zealand - Bray, Jonathan (Massey University, 2020)
Soft tissue sarcoma (STS) are tumours derived from tissues of mesenchymal origin. Local recurrence of the tumour following surgical resection is the characteristic challenge in the management of STS. There are currently no prognostic tests that can reliably predict which tumours have a higher or lower risk of recurrence. The aim of the studies contained in this thesis was to investigate aspects of STS biology to identify new prognostic markers. A large archive of STS was established with patient outcomes determined by questionnaire. Tissue was subsequently analysed using immunohistochemistry and reverse transcriptase-polymerase chain reaction to understand the role of two molecules – vascular endothelial growth factor (VEGF) and decorin – in influencing tumour behaviour. This study revealed that when the tissue stroma surrounding the tumour cells had a strong immunostaining intensity for decorin, the risk of tumour-related death was significantly reduced. In addition, STS with a high immunostaining for VEGF were more than 7 times more likely to recur, and 5 times more likely to cause the death of the dog. When the immunostaining characteristics for VEGF and decorin were combined with other patient and tumour features into a predictive algorithm called a nomogram, it was possible to determine, with almost 100% accuracy, which dogs would remain disease-free 3 years after surgery. The importance of VEGF in the progression of tumour growth was subsequently demonstrated by treating dogs with haemangiosarcoma (HSA) – a mesenchymal tumour with many characteristics similar to STS – with thalidomide. Thalidomide is a potent antagonist of VEGF, but also has a number of other modulating influences on the tumour microenvironment. Dogs treated with thalidomide survived significantly longer than dogs that did not receive this drug, suggesting that thalidomide can slow the ability for residual microscopic tumour cells to develop into a grossly visible, and life-threatening tumour. An analysis of metastatic lesions that developed in dogs treated with thalidomide revealed that immunostaining for VEGF was significantly reduced. This suggests that thalidomide may be a useful adjuvant therapy for dogs with STS that are considered to be at high risk of recurrence after surgery, as determined by their VEGF immunostaining intensity.
Keywords: Dogs; Diseases; Sarcoma; Soft tissue tumors; Prognosis; 300907 Veterinary medicine (excl. urology); 321111 Solid tumours